Hubungan Faktor Individu dengan Tingkat Stres pada Pekerja Pabrik Tekstil PT. X Kota Tangerang - Refi Maya Arlita; Mia Kusmiati; Nurul Annisa Abdullah (Bandung Conference Series: Medical Science, 2022)
Abstract. Mental health is an important aspect to achieve overall health. Mental health is just as important as physical health. Excessive and uncontrollable stress can cause fatigue, which is a combination of physical, mental and emotional exhaustion. Job stress is an emotional state that arises because there is a mismatch between the level of demand and the individual's ability to cope with the work stress it faces. Work stress experienced by female and male employees can be different. Stress is also determined by the individual himself with various risk factors experienced such as age, gender, marital status, and years of service. This study aims to determine the relationship of individual factors with stress levels in textile factory workers at PT. X Tangerang City. This study used a cross-sectional method with an observational analysis approach. There are 122 individual data that meet the inclusion criteria, respondents were asked to fill out the DASS-42 questionnaire to assess the level of stress in workers. Individual characteristics of textile factory workers at PT. X in Tangerang City were the most, aged 18-33 years (62.3%), female (60.66%), with married status (53.28%) and having a working period of < 5 years (59 ,56%). Description of stress levels in textile factory workers at PT. X in Tangerang City shows that most workers do not experience stress. The rest are based on the highest order in the category of heavy-very heavy (15.5%), mild (14.7%) and moderate (10.7%). Data from the study found that there was no relationship between the age of workers and stress levels (p value = 0.08), gender of workers with stress levels (p value = 0.102), marital status of workers with stress levels (p value = 0, 12) and there is a relationship between individual factors of tenure and stress levels (p value = 0.002). Abstrak. Kesehatan mental merupakan aspek penting untuk mencapai kesehatan secara keseluruhan. Kesehatan mental sama pentingnya dengan kesehatan fisik. Stres yang berlebihan dan tidak terkendali dapat menyebabkan kelelahan, yang merupakan kombinasi dari kelelahan fisik, mental dan emosional. Stres kerja merupakan keadaan emosional yang timbul karena ada ketidaksesuaian antara tingkat permintaan dengan kemampuan individu untuk mengatasi stres kerja yang dihadapinya. Stres kerja yang dialami oleh karyawan wanita dan pria bisa jadi berbeda. Stres ditentukan juga dari individu itu sendiri dengan berbagai faktor risiko yang dialami seperti usia, jenis kelamin, status pernikahan, dan masa kerja. Penelitian ini bertujuan untuk mengetahui hubungan faktor individu dengan tingkat stres pada pekerja pabrik tekstil PT. X Kota Tangerang. Penelitian ini menggunakan metode cross-sectional dengan pendekatan analisis observasional. Terdapat 122 data individu yang memenuhi kriteria inklusi, responden diminta untuk mengisi kuesioner DASS-42 untuk menilai tingkat stres pada pekerja. Karakteristik individu pekerja pabrik tekstil PT. X di Kota Tangerang yang paling banyak yaitu, usia 18-33 tahun (62,3%), berjenis kelamin perempuan (60,66%), dengan status sudah menikah (53,28%) dan memiliki masa kerja < 5 tahun (59,56%). Gambaran tingkat stres pada pekerja pabrik tekstil PT. X di Kota Tangerang menunjukkan sebagian besar pekerja tidak mengalami stres. Sisanya berdasarkan urutan terbanyak pada kategori berat-sangat berat (15,5%), ringan (14,7%) dan sedang (10,7%). Data dari penelitian didapatkan bahwa tidak terdapat hubungan antara usia pekerja dengan tingkat stres (p value = 0,08), jenis kelamin pekerja dengan tingkat stres (p value = 0,102), status pernikahan pekerja dengan tingkat stres (p value = 0,12) dan terdapat hubungan antara faktor individu masa kerja dengan tingkat stres (p value = 0,002).